A Framework for Hazard Analysis of Safety-Critical Computer Controlled Systems - Kumar, Kadupukotla Satish; Ramaiah, Panchumarthy Seetha (IJRDO -Journal of Computer Science Engineering, 2016)
Safety-Critical Computer Controlled Systems (SCCCS) are those systems whose failure could result in loss of life, significant property damage, or damage to the environment. There are many well known examples in application areas such as medical devices, aircraft flight control, weapons, and nuclear systems. These systems consist of a set of functional elements, controlled by embedded processors that together achieve a common objective. Most softwarerelated accidents occurred in SCCCS by executing flawed programming and instructions. The research literature currently lacks an appropriate safety analysis and is fragmented among activities. The aim of this paper is to reduce the probability of unsafe system conditions using a variety of management, organization and technical measures. The approach begins with conducting three different types of hazard analysis techniques to SCCCS such as Software Failure Mode and Effects Analysis (SFMEA), Software Fault Tree Analysis (SFTA) and Systems-Theoretic Process Analysis (STPA). In this paper, the application of systems-theoretic approach is implemented on Ball Position Control System (BPCS) and performed the comparison between traditional methods and systemic methods for analysis and design. The proposed systems-theoretic approach can be applied to SCCCS in diverse sectors to identify and control the identified hazards. There is clear value in developing a systems-theoretic approach to safety analysis in SCCCS. Development of a SCCCS based on our proposed software safety approach significantly enhanced the safe operation of the overall system.